Eliminating the Phenomenon of Sleeping Assets: Productive Diversification Strategy and Nazir Competency Standardization as Pillars of Community Welfare - Nurhayati (JURNAL ILMIAH GEMA PERENCANA, 2026)
Optimizing waqf assets in Indonesia currently faces a serious obstacle in the form of a large proportion of idle land that has not been diversified into productive sectors. This phenomenon is rooted in the strong dominance of traditional and consumerist paradigms in society, which is exacerbated by low socio-economic fiqh literacy at the grassroots level. This condition limits the understanding of waqf to purely religious and social functions, thus failing to create sustainable economic added value for the welfare of the community. The policy methodology used in this study is a descriptive-qualitative approach with a multiple criteria analysis. Identification of priority problems was carried out using the USG (Urgency, Seriousness, Growth) method. Based on the USG analysis, the problem of the dominance of idle land and low productive diversification was determined as the main priority with the highest score (15). Next, four policy alternatives were evaluated using Eugene Bardach's Eight-Path Model, considering the criteria of effectiveness, efficiency, political acceptability, and technical feasibility. The results of the scoring analysis indicate that the policy alternative of providing tax incentives and facilitating licensing for waqf-based businesses is the most effective option with the highest total score (17). Therefore, this article recommends that the Minister of Religious Affairs issue a Joint Decree to transform the waqf paradigm into a competitive business model by attracting investors through fiscal incentives. Implementing this recommendation is expected to break the deadlock in optimizing idle land and encourage waqf's tangible contribution to national welfare.